2003
DOI: 10.1111/j.1550-7408.2003.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Cytoskeletal Proteins in the Cortex of Tetrahymena1

Abstract: An important unsolved problem lies in the mechanisms that determine overall size, shape, and the localization of subcellular structures in eukaryotic cells. The membrane skeleton must play a central role in these processes in many cell types, and the ciliate membrane skeleton, or epiplasm, offers favorable opportunities for exploring the molecular determinants of cortical organization. Among the ciliates, Tetrahymena is well suited for the application of a wide range of molecular and cellular approaches. Progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Using sophisticated immunological procedures, Huttenlauch et al (1998) have demonstrated the individuality of the two classes and have established the presence of both in Euglena , the dinoflagellate Amphidinium , and the ciliates Pseudomicrothorax, Paramecium, Tetrahymena , and Euplotes . The major proteins in the epiplasm of Tetrahymena , however, are proteins unrelated to these called EpiA, EpiB, and EpiC (Honts and Williams 2003; Williams et al 1995). These three proteins are present in large amounts and show overlapping but independent distributions in the epiplasm of the cell.…”
mentioning
confidence: 99%
“…Using sophisticated immunological procedures, Huttenlauch et al (1998) have demonstrated the individuality of the two classes and have established the presence of both in Euglena , the dinoflagellate Amphidinium , and the ciliates Pseudomicrothorax, Paramecium, Tetrahymena , and Euplotes . The major proteins in the epiplasm of Tetrahymena , however, are proteins unrelated to these called EpiA, EpiB, and EpiC (Honts and Williams 2003; Williams et al 1995). These three proteins are present in large amounts and show overlapping but independent distributions in the epiplasm of the cell.…”
mentioning
confidence: 99%
“…Curtenaz et al. ; Honts and Williams ; Keryer et al. ), is that antisera may be reacting with covalent modifications or particular motifs (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous kinetosome‐associated proteins in the cortex of various ciliates have been described (Fleury et al. ; Honts and Williams ; Jerka‐Dziadosz et al. ; Keryer et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the addition of calcium to a macrostomal population initiates cytopharyngeal pouch closure and subsequent food vacuole formation (Sherman, Buhse, and Smith 1981). It is especially intriguing that actin and centrin complexes have both been reported to contract in the presence of calcium (Huxley 1969; Salisbury et al 1984), and it has not escaped our attention that tetrins share some structural similarity with coiled‐coil actin‐binding proteins, such as myosin and spectrin (Brimmer and Weber 2000; Honts 1991; Honts and Williams 2003). With this in mind, it is also intriguing that MYO1, a myosin identified in Tetrahymena thermophila , has been localized by indirect immunofluorescence to the “basal bodies and associated fibrillar material in the oral apparatus” (Garces, Hoey, and Gavin 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Anti‐tetrin antibodies have been localized by indirect im‐munofluorescence to the CC and at the ultrastructural level to a filamentous structure associated with the undulating membrane in Tetrahymena pyriformis (Dress et al 1992). Tetrins are considered novel Tetrahymena proteins, though some similarity has been noted with other coiled‐coil proteins, such as heavy chain myosins and spectrins (Brimmer and Weber 2000; Honts 1991; Honts and Williams 2003). …”
mentioning
confidence: 99%